1989
DOI: 10.1897/1552-8618(1989)8[1067:gvilaf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Laboratory and Field Populations of the Midge, Chironomus Tentans Fab.: Implications for Toxicology

Abstract: Chironomus tentans larvae are used extensively in toxicoiogical bioassays. Gel electrophoresis was performed on seven laboratory populations and a wild population of C. tentans. Direct count heterozygosity was significantly different between wild and laboratory populations, as well as among laboratory populations. Percent polymorphic loci demonstrated the same trends but were marginally nonsignificant. The wild midge population had seven unique alleles and a significantly higher level of heterozygosity. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
(8 reference statements)
1
13
0
Order By: Relevance
“…Chironomus species usually account for at least 50% of the combined macroinvertebrate species composition on any given freshwater ecosystem (97). Chironomids are common and have an holarctic distribution, they are relatively sedentary and thus representative of local conditions, and larvae may accumulate metals in a manner directly proportional to environmental conditions (41,57,98 (57), and Harrahy et al (98). A. aegypti were reared as described by Raymes-Keller et al (99).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chironomus species usually account for at least 50% of the combined macroinvertebrate species composition on any given freshwater ecosystem (97). Chironomids are common and have an holarctic distribution, they are relatively sedentary and thus representative of local conditions, and larvae may accumulate metals in a manner directly proportional to environmental conditions (41,57,98 (57), and Harrahy et al (98). A. aegypti were reared as described by Raymes-Keller et al (99).…”
Section: Methodsmentioning
confidence: 99%
“…A. aegypti were reared as described by Raymes-Keller et al (99). The basic protocol was to expose C. tentans or A. aegvpti larvae to predetermined sublethal doses of heavy metals (41,57,98). Each experiment was conducted in duplicate; 50 to 100 fourth instar larvae were placed in receptacles filled with 200 ml dechlorinated tap water containing either 50 or 500 ppb Cd (or other metals such as Hg) and Cu, or their binary and trinary combinations, in the case of A. aegypti, or no metal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been demonstrated that conditions in the laboratory environment may cause unanticipated alterations in the population's genetic structure such as changes in allele frequency, loss of alleles, and diminished heterozygosity. These changes could result from founder events, genetic drift, nonrandom mating, and artificial selection [1].…”
Section: Introductionmentioning
confidence: 99%